CB2-Selective Cannabinoid Receptor Ligands: Synthesis, Pharmacological Evaluation, and Molecular Modeling Investigation of 1,8-Naphthyridin-2(1H)‑one-3-carboxamides - Lucchesi, Valentina; Hurst, Dow P; Shore, Derek M; Bertini, Simone; Ehrmann, Brandie M; Allarà, Marco; Lawrence, Lyle; Ligresti, Alessia; Minutolo, Filippo; Saccomanni, Giuseppe; Sharir, Haleli; Macchia, Marco; et al. (Journal of medicinal chemistry, 2014)
We have recently identified 1,8-naphthyridin-2(1H)-one-3-carboxamide as a new scaffold very suitable for the development of new CB2 receptor potent and selective ligands. In this paper we describe a number of additional derivatives in which the same central scaffold has been variously functionalized in position 1 or 6. All new compounds showed high selectivity and affinity in the nanomolar range for the CB2 receptor. Furthermore, we found that their functional activity is controlled by the presence of the substituents at position C-6 of the naphthyridine scaffold. In fact, the introduction of substituents in this position determined a functionality switch from agonist to antagonists/inverse agonists. Finally, docking studies showed that the difference between the pharmacology of these ligands may be in the ability/inability to block the Toggle Switch W6.48(258) (χ1 g+ → trans) transition.